The Behavior of Money National Income under Inflationary Conditions - Smithies, A. (Quarterly Journal of Economics, 1942)
The problem, 113. — Definitions and assumptions, 114. — The Keynesian method: the upper limit, 115; the speed, 119; the influence of exogenous factors, 120. — The Tinbergian method: the question of limit, 121; of speed, 125. — Numerical example, 126. — Conclusion, 127.